(untitled) (Ukrainian Journal of Ophthalmology, 2025)
The emergence of fundamentally novel technological solutions in the field of gene therapy today, the formation of the priority and the development of genetic technologies create serious prerequisites for the beginning of a new Fusion era in ophthalmology in the near future. This review, in its first part, presents the results of fundamental and clinical studies on the use of viral and non-viral systems for the delivery of genetic material in ophthalmology. The second part of the review will focus on genetic therapeutic strategies (gene replacement, gene suppression, genomic editing using CRISPR / Cas9 technology, priming and transposon editing) that have been used in ophthalmology over the past several years.